The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1016/j.neuroimage.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of what or where reduces brain activity, but a bottleneck occurs when both are predictable

Abstract: Detecting regularities in the sensory environment licenses predictions that enable adaptive behaviour. However, it is unclear whether predictions about object category, location, or both dimensions are mediated by overlapping systems, and relatedly, whether constructing predictions about both category and location is associated with processing bottlenecks. To examine this issue, in an fMRI study, we presented participants with image-series in which non-deterministic transition probabilities enabled predictions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 97 publications
2
25
1
Order By: Relevance
“…Later work (Davis & Hasson, 2016) corroborated this conclusion but further suggested that processing regularity in independent dimensions is not modular (where "processing" holistically refers to the updating of statistical information, generation of predictions and prediction-error terms). Specifically, that work examined neural responses to stimuli where, over a stimulus series, the location of a subsequent visual image or its semantic category were either predictable or not.…”
Section: Sensitivity To Regularity In Multimodal Contextsmentioning
confidence: 95%
See 1 more Smart Citation
“…Later work (Davis & Hasson, 2016) corroborated this conclusion but further suggested that processing regularity in independent dimensions is not modular (where "processing" holistically refers to the updating of statistical information, generation of predictions and prediction-error terms). Specifically, that work examined neural responses to stimuli where, over a stimulus series, the location of a subsequent visual image or its semantic category were either predictable or not.…”
Section: Sensitivity To Regularity In Multimodal Contextsmentioning
confidence: 95%
“…For deterministic sequential information, individuals are able to track two independent information streams without observable behavioral costs (e.g., Mayr, 1996). Neuroimaging studies show that individuals spontaneously track statistical features of different stimulus dimensions (e.g., category and location or shape and color; Aizenstein et al, 2004;Davis & Hasson, 2016). It is unclear, however, whether there are brain systems that holistically integrate statistical information across different modalities when exposed to multimodal inputs.…”
Section: Introductionmentioning
confidence: 99%
“…For one, the AI, dACC and dlPFC activate synchronously in response to uncertainty in the environment; these regions overlap with areas implicated in negative mood states (Feinstein et al, 2006; Naqvi and Bechara, 2009; Davis and Hasson, 2016). The dACC and AI activate together during decision-making; co-activation has been shown to increase with task difficulty and stimulus ambiguity.…”
Section: Anatomy and Function Of The Sn Cortico-striatal Loopmentioning
confidence: 99%
“…This question is particularly interesting given that the higher-order regions in frontal cortex containing spatial and feature information may be largely separate5. It is currently unknown whether these regions operate independently, or whether they can synergistically induce top-down modulations in early visual cortex that are both spatially and feature specific67. That is, whether feature-based expectation can affect processing of stimuli at the location in which the stimulus is expected to occur, without affecting processing of stimuli presented elsewhere in the visual field.…”
mentioning
confidence: 99%